Optimisasi Sistem Antrian di Era Pandemi untuk Meningkatkan Kinerja Pelayanan Stasiun Pengisian Bahan Bakar Umum (SPBU) - Ats-Tsauri, Muhammad Ibrahim; Siddik, Abdullah Fawzy; Wiyatno, Tri Ngudi (JURNAL TEKNIK INDUSTRI, 2022)
From the results of observations at petrol station 34–17521 South Tambun, it was found that in a certain period there were queues exceeding the service standard of petrol stations causing customers to leave the queue. This study aims to measure the performance of gas station queues and propose a queuing line system optimization strategy with Multi Channel Single Phase (M/M/S) queuing model. Collect data using in -depth observations and interviews. Queuing data was taken for two weeks during the COVID-19 pandemic, daily from 06.00 to 20.00 WIB. From the results of the study, service optimization strategy is proposed with 3 channels at 17.00 - 18.00 WIB and 2 channels at 06.00 - 07.00, 12.00 - 13.00, 16.00 - 17.00, and 18.00 - 19.00 to reduce the number of queues at 18.00 - 19.00. to achieve gas station performance targets and maintain customer satisfaction.